High-quality genome assembly and genetic mapping reveal a gene regulating flesh color in watermelon (Citrullus lanatus) - Nie, Hualin; Kim, Moonkyo; Lee, Sanghee; Lim, Sohee; Lee, Mi Sun; Kim, Ju Hyeok; Noh, Sol Ji; Park, Seong Won; Kim, Sang-Tae; Shin, Ah-Young; Lee, Yi; Kwon, Suk-Yoon (Frontiers in Plant Science, 2023)
The unique color and type characteristics of watermelon fruits are regulated by many molecular mechanisms. However, it still needs to be combined with more abundant genetic data to fine-tune the positioning. We assembled genomes of two Korean inbred watermelon lines (cv. 242-1 and 159-1) with unique color and fruit-type characteristics and identified 23,921 and 24,451 protein-coding genes in the two genomes, respectively. To obtain more precise results for further study, we resequenced one individual of each parental line and an F2 population composed of 87 individuals. This identified 1,539 single-nucleotide polymorphisms (SNPs) and 80 InDel markers that provided a high-density genetic linkage map with a total length of 3036.9 cM. Quantitative trait locus mapping identified 15 QTLs for watermelon fruit quality-related traits, including β-carotene and lycopene content in fruit flesh, fruit shape index, skin thickness, flesh color, and rind color. By investigating the mapping intervals, we identified 33 candidate genes containing variants in the coding sequence. Among them, Cla97C01G008760 was annotated as a phytoene synthase with a single-nucleotide variant (A → G) in the first exon at 9,539,129 bp of chromosome 1 that resulted in the conversion of a lysine to glutamic acid, indicating that this gene might regulate flesh color changes at the protein level. This findings not only prove the importance of a phytoene synthase gene in pigmentation, but also explains an important reason for the color change of watermelon flesh.